Pattern of mortality in sickle cell disease: an autopsy study - Shah, Pinkal; Bhagat, V. M.; Patel, Komal; Patel, Chandani (International Journal of Research in Medical Sciences, 2017)
Background: Sickle haemoglobin is highly prevalent in western India. Sickle cell disease (SCD) is the generic term for the group of haemoglobinopathies caused by the occurrence of haemoglobin S (Hbs) in the homozygous form –sickle cell anaemia (Hbss) or as the heterozygous combination of Hbs with another abnormal haemoglobin such as Hbsc or beta –thalassaemias (Hbs b-thal). While doing autopsy in case of death with no apparent cause, the possibility of death may be due to vaso-occlusive crisis in sickle cell disease should be kept in mind. The findings at autopsy are variation of features which may or may not be directly connected to death. The goal is to draw awareness among physicians and relatives on need of autopsy as to minimize future unexpected death from complication or crisis and to enhance knowledge on both parties. Methods: This was a study of autopsy specimens received between January 2015 to December 2015 at tertiary care hospital. Results: Total of 679 autopsy cases were received, out of which sickled erythrocytes were detected in 25 cases. The mean age at death was 30 years, a male/female ratio of 1.5:1 and peak mortality was in the 2nd to 4th decades of life. The commonest presentation was sudden death. The cause of death in middle aged patients were vaso occlusive crisis, in paediatric patients were infection and in older patients were chronic organ damage. Conclusions: Early diagnosis, prompt treatment and extended screening programme are necessary in prevalent tribal belt of western India to reduce morbidity and mortality. we should also introduce awareness programmes in tribal belt of western India.